Estimation of Morphological Tables Using Text Analysis Results - Illia Savchenko (Computer Science Journal of Moldova, 2016)
This paper proposes methods for obtaining input data, necessary for the modified morphological analysis method, from the text sources of data using text analysis tools. Several methods are described that are suitable for calculating initial estimates of alternatives and cross-consistency matrix values based on processing text fragments by rule-based categorization and sentiment analysis tools. A practical implementation of this tool set for assessing statements in news regarding Ukraine is considered.